Influence of the strain hardening behaviour on the tensile and compressive response of aluminium auxetic structures. (1st February 2023) - Sabari, S.; Andrade, D.G.; Leitão, C.; Simões, F.; Rodrigues, D.M.
Highlights: 2D and 3D metallic auxetics are studied numerically and experimentally. The base materials hardening behaviour is characterized. The role of hardening behaviour on auxeticity is analysed. In tension the hardening behaviour determines the failure mode of the auxetics. In compression it determines the buckling behaviour and the Poisson ratio. Abstract: The performance of the metallic auxetics relies on the plastic deformation behaviour of the base materials, however, this topic is rarely reported in the literature. To address this issue, a coupled experimental and numerical analysis, on the tensile and compressive behaviour of re-entrant cell auxetics, made of AA2017, AA5083, AA6082 and AA7075 aluminium alloys, was performed. The base materials were tested in tension and the main differences in hardening behaviour between them were identified. From the analysis, it was concluded that in tension, the strain hardening behaviour at the onset of failure has a strong influence on the auxetics strength and failure mode, but not on the Poisson ratio. From the compressive analysis, it was concluded that the base materials hardening behaviour have a strong influence on the auxeticity of the structures, determining the occurrence of buckling, the energy absorbing capability of the structure and the Poisson ratio evolution during loading.